2020
DOI: 10.1371/journal.pone.0235173
|View full text |Cite
|
Sign up to set email alerts
|

Health care access of informal waste recyclers in Johannesburg, South Africa

Abstract: Introduction Informal waste recyclers contribute significantly to waste removal in South Africa. Waste recyclers face health hazards which are associated with handling and disposal of waste, a lack of personal protective wear and inaccessibility to occupational health care services. Consequently, accessing health care within the public health care sector is important for health outcomes in this population. This study assesses health care access of informal waste recyclers in South Africa to establish baseline … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Migrant undocumented workers may not feel welcome at health facilities [ 5 , 6 ]. Additionally, informal economy workers may have less access to occupational health education and services; resulting in less knowledge of hazards and their control, poor access to personal protective equipment, and low health services coverage [ 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Migrant undocumented workers may not feel welcome at health facilities [ 5 , 6 ]. Additionally, informal economy workers may have less access to occupational health education and services; resulting in less knowledge of hazards and their control, poor access to personal protective equipment, and low health services coverage [ 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our study found that distance (no health facility nearby since a local hospital was moved), cost (have to take a taxi to nearest health facility), clinic times and queues (street vendors unable to wait for long as the operating times coincide with their trading times) are main challenges in accessing health care, showing consistency with findings of other studies. 22,40 Though condom provision at the workplace is not mandatory in South Africa, the HIV policies advocate that workplaces facilitate easy access to condoms for workers, as part of HIV primary prevention. 41 According to our findings more needs to be done for marketplace vendors to ensure that they have the suggested easy access to condoms.…”
Section: Discussionmentioning
confidence: 99%
“…Against the backdrop of these risks, however, waste pickers have low health-seeking behaviour [ 25 , 40 ]. All informal workers suffer from a ‘no work no pay’ situation, and this can make waste pickers reluctant to seek medical attention for work-related injuries.…”
Section: Occupational Hazards In the Inner Citymentioning
confidence: 99%